Estudo de Coprodutos da produção de biocombustível - Pinto, Helen Ramalho de Farias (2014)
The biomass has attracted much attention because it is a renewable source of energy. Cotton seed and cassava (shaving) were dried in convective tunnel to dehydrate and achieve humidity around 11%. The use of cotton (Gossypium hirsutum L.) and cassava for biofuel production (biodiesel and ethanol) is presented as a promising alternative due to the production of its fruits being perennial crops and the potential coproducts available. The study was conducted to evaluate the technical feasibility of combinations of coproducts of the production of these biofuels for sustainable sourcing of feed input. Biodiesel is a clean fuel because it is biodegradable, non-toxic and reduces emissions of air pollutants. The oil content of cotton seed used in obtaining biodiesel reaches an average of 25% yield. The average levels of cottonseed oil found in tests applying herbaceous cotton seed was 23% in the core deslintado 37% and 12% cottonseed meal. The physico-chemical properties of cottonseed oil made their indices within the recommended technical standards, which were acid value in oleic acid 0.17 mgNaOH/g, peroxide index 10 meq/kg oil and iodine 103 g/100g. The results of the tests bromatologics pie from the extraction of cottonseed oil reached analytical standards with 50% carbohydrates, 24% crude protein, ash 4% and 12% lipids. Cassava (Manihot esculenta Crantz) is widely grown for animal feed in Brazil. The coproduct of cassava root has a low oil content (average 1.3%) and high carbohydrate content (average 75%). In this experiment, when the merger of coproducts in the tests, certain aspects were considered for the formulations edible mixtures calculated for animal, the main being the chemical composition of foods (coproducts), the nutritional requirements of each type of animal and the effects antinutritional of gossypol and hydrocyanic acid, respectively, present in cotton and manioc. The bromatologics results of coproducts, combined with the nutritional requirements of each animal entered the calculations of the composition of the food mix created. The metabolizable energy and digestive food were measured, to meet the nutritional needs of animals in categories: bird, bovine (calf, calf and mother in lactation), goats, sheep and pigs. The mixture prepared n°4 was chosen to nourish cattle (in lactation) for a period of 90 days. The test animals were six dairy crossbred cows, weighing between 400 and 500 kg/head/body weight. The ratio applied forage to concentrate the feed composition was held in level 63:37, 20% crude protein. Nutritional assessment of the animals was obtained an increase of twenty percent in milk production and improvements in physical performance of carcasses of animals and their offspring.